Evaluation of Hybrid Seeds of Three-Way and Single Cross for Grain Number and Weight in Bread and Durum Wheat - Mustafa Yıldırım; Mustafa Çakmak (Turkish Journal of Agriculture: Food Science and Technology)
The hybrid seeds obtained by crossing in wheats should be heavier and a greater number of grains per combination because of more variation and to created powerful plants for next year generations. Therefore, this study was conducted during the winter growing season of 2005-2006 in Transitional Zone Agricultural Research Institute in Eskişehir and to determine the hybrid seeds of single cross and three-way cross compared to each other for 10-grains weight (TGW) and grain number per combination (GC) in separately bread wheat and durum wheat. 224 F1s for single cross and 326 F1s for three-way cross in bread wheat and 56 F1s for single cross and 66 F1s for three-way cross in durum wheat were produced. According to results, GC and TGW in bread wheats were higher values than durum wheats both in single cross and three-way cross. The GC values in three-way cross had higher variation (68.9%) compared the others. The separately mean of GC and TGW of hybrids in single cross both in bread and durum wheat were lower than the means of hybrids in three-way cross (with ratios of 32% and 16.7%, respectively). In brief: three-way cross had more performance for studied traits in wheat hybrids compared to single cross. The reason of such an outcome can be demonstrated in the future by genetic studies.